Estuarine hydrodynamic as a key-parameter to control eutrophication processes - Duarte, António A. L. Sampaio (2009)
Estuaries and coastal lagoons are commonly subjected to intensive anthropogenic stress due to massive pollutant loading from urbanised riparian areas. Nutrient enrichment is a key-factor for habitat degradation, leading to sensible structural changes in estuarine ecosystems with the consequent occurrence of eutrophication processes. The influence of hydrodynamics must not be neglected on estuarine eutrophication vulnerability assessment. In fact, flushing time affects the transport and the permanence of water and its constituents inside an estuary, so the increase of estuarine flushing capacity can be seen as a management measure to mitigate or to invert eutrophication processes, like the one observed in the Mondego River estuary (Portugal), during the last two decades. In this work, an integrated 2-DH water quality model was applied to calculate water residence time values, at different simulated management scenarios of the Mondego estuary. The results of the performed simulations illustrate the strong assymmetry of flood and ebb duration time at the inner sections of this estuary, a keyparameter for a correct tidal flow estimation, as the major driving force of the southern arm flushing capacity, as well as a spatial and temporal variability of calculated RT values. The conclusions of this work confirm the crucial influence of hydrodynamics on estuarine water quality status and the usefulness of this hydroinformatic tool as contribution to support the design of a sustainable management plan, based on nutrient loads reduction and hydrodynamic circulation improvement. So, the proposed methodology, integrating hydrodynamics and water quality, constitutes a powerful hydroinformatic tool for enhancing estuarine eutrophication vulnerability assessment, in order to contribute for better water quality management practices and to achieve a true sustainable development.